COVID-19 Pandemic as an Excellent Opportunity for Global Health Diplomacy - Taghizade, Sanaz; Chattu, Vijay Kumar; Jaafaripooyan, Ebrahim; Kevany, Sebastian (Frontiers in Public Health, 2021)
Undoubtedly, the COVID-19 pandemic is not the first and most frightening global pandemic, and it may not be the last. At the very least, this phenomenon has though seriously challenged the world's health systems; it has created a new perspective on the value of national, regional, and international cooperation during the crises. The post-coronavirus world could be a world of intensified nationalist rivalries on the economic revival and political influence. However, the strengthening of cooperation among nations at different levels will lead to the growth of health, economy, and security. The current situation is a touchstone for international actors in coordinating the efforts in similar future crises. At present, this pandemic crisis cannot be resolved except through joint international cooperation, global cohesion, and multilateralism. This perspective concludes that the pandemic could be an excellent opportunity for the scope of global health diplomacy (GHD) and how it can be applied and practiced for strengthening five global arenas, namely 1) international cooperation and global solidarity, 2) Global Economy, Trade and Development, 3) Global Health Security, and 4) Strengthening health systems and 5) Addressing inequities to achieve the global health targets. GHD proves to be very useful for negotiating better policies, stronger partnerships, and achieving international cooperation in this phase with many geopolitical shifts and nationalist mindset among many nations at this stage of COVID-19 vaccine roll-out.